The Role of Online Reviews in Shaping Consumer Trust and Purchase Decisions on Shopee - Az-zahra, Nadya Sabrina; Fakhira, Faza; Putri, Meisya Salsabila; Situmorang, Yunus; Zakiah, Rizka (Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This study explores the role of online reviews in shaping consumer trust and influencing purchase decisions on the Shopee platform. Using a quantitative survey approach, data were collected from Shopee users to analyze how review credibility, quality, and sentiment affect consumer perceptions and decision-making. The results show that credible and positive reviews significantly enhance consumer trust, which subsequently increases the likelihood of purchase decisions. These findings reveal that online reviews serve not only as sources of information but also as social validation that reinforces consumers’ confidence in online transactions. The study underscores the strategic importance of authentic and transparent review management in strengthening consumer trust and driving purchasing behavior in e-commerce.